Quantifying technical actions in professional soccer using foot-mounted inertial measurement units - Marris, J.; Barrett, S.; Abt, G.; Towlson, C. (Science and Medicine in Football, 2022)
Objectives: This study aimed to (i) establish the concurrent validity and intra-unit reliability of a foot-mounted inertial measurement unit for monitoring soccer technical actions, (ii) quantify the within-microcycle inter-positional differences in the technical actions of professional soccer training, and (iii) determine the influence of drill category on the technical actions of professional soccer training.